Rail Transport - An Important Factor in the Port of Rijeka Development - Hlača, Bojan; Rudić, Dušan; Hirnig, Saša (Promet - Traffic&Transportation, 2012)
The economic situation and comparative advantages of the Port of Rijeka are no more than important preconditions of its development and competitive ability. No adequate connection of the Port of Rijeka to its catchment area is possible without a modern rail and road traffic. The researches and analyses of the port hinterland connection current state, the results of which are provided in these documents, clearly indicate the need to upgrade the existing railway tracks and build a new level Rijeka – Zagreb railway line. This line is a vital condition for ensuring both, a strong growth of the port performances and its competitive ability vis-a-vis other neighbouring ports. The level railway line Rijeka – Zagreb with Rijeka railway junction adequately upgraded, should be therefore regarded as strategic traffic project and conditio sine qua non for the future development of the Port of Rijeka. However, no solution of the Rijeka railway junction problem will be possible without finding the right way for better connection of some of the port terminals. When considering the integral solution of the rail traffic in the greater Rijeka Basin, it is important to know that the access to individual port terminals, the connection with the railway in Istria through the Učka Tunnel and connection with the port terminals on the Island of Krk are of great importance for the Port of Rijeka future development. The efforts to recognize the problems in the port environment and define priorities that make the rail transport a key factor of the Port of Rijeka’s future growth, are the main contributions of this study. KEY WORDS: Port of Rijeka, traffic connections, rail traffic, Rijeka railway junction, development guidelines